CELF1/p53 axis: a sustained antiproliferative signal leading to villus atrophy under total parenteral nutrition. Issue 3 (4th December 2018) - Yan, Jun-Kai; Zhang, Tian; Dai, Li-Na; Gu, Bei-Lin; Zhu, Jie; Yan, Wei-Hui; Cai, Wei; Wang, Ying
ABSTRACT: Intestinal villus atrophy is a major complication of total parenteral nutrition (TPN). Our previous study revealed that TPN‐induced villus atrophy is accompanied by elevated expression of CUGBP, Elav‐like family member 1 (CELF1); however, its mechanism of action has not been fully understood. Herein, we report a pivotal role of CELF1/p53 axis, which induces a sustained antiproliferative signal, leading to suppressed proliferation of intestinal epithelial cells (IECs). By using a rat model of TPN, we found synchronous upregulation of CELF1 and p53 in jejunum mucosa, accompanied by a 51% decrease in crypt cell proliferation rate. By using HCT‐116 cells as an IEC model in vitro, we found that the expression of CELF1 altered dynamically in parallel to proliferation rate, suggesting a self‐adaptive expression pattern in IECs in vitro . Furthermore, ectopic overexpression of CELF1 elicited a significant antiproliferative effect in HCT‐116, Caco‐2, and IEC‐6 cells, whereas knockdown of CELF1 elicited a significant proproliferative effect. Moreover, cell‐cycle assay revealed that ectopic overexpression of CELF1 induced sustained G2 arrest and G1 arrest in HCT‐116 and IEC‐6 cells, respectively, which could be abolished by p53 silencing. Mechanistically, polysomal profiling and nascent protein analysis revealed that regulation of p53 by CELF1 was mediated through accelerating its protein translation in polysomes. Taken together, our findings revealed a sustained suppression of IEC proliferation evoked by CELF1/p53 axis, which may be a potential therapeutic target for the treatment of TPN‐induced villus atrophy.—Yan, J.‐K., Zhang, T., Dai, L.‐N., Gu, B.‐L., Zhu, J., Yan, W.‐H., Cai, W., Wang, Y. CELF1/p53 axis: a sustained antiproliferative signal leading to villus atrophy under total parenteral nutrition. FASEB J. 33, 3378–3391 (2019). www.fasebj.org